How Important Is the Efficiency of Government Investment? The Case of the Republic of Congo - Nielsen, Hannah; Lofgren, Hans (2012)
The Republic of Congo, an oil rich country in Central Africa, has made substantial progress in the past decade in stabilizing the economy and achieving high growth rates. However, despite reaching middle-income country status in 2006, the economy is not diversified, poverty remains pervasive, and social indicators are well below the average for countries with a similar income level. This paper analyzes aspects of an ambitious investment program on which the government has embarked to improve the provision of basic services and promote private sector development. The success of this program, however, is questionable given the low absorptive capacity of the country and in particular the poor efficiency of public investment management. The analysis is based on simulations with an economy-wide model for analysis of development strategies and government policies, MAMS (Maquette for MDG Simulations). The results of the simulations show that slightly delaying large investment projects, while simultaneously improving the efficiency of the investment program, would lead to significantly higher growth rates and lower poverty levels. The analysis therefore confirms the importance of efficient public investment management for the optimal use of the country's resources.